Impact of more conservative European Society of Cardiology guidelines on the management of patients with acute chest pain. Issue 6 (15th March 2021) - Kienbacher, Calvin L.; Fuhrmann, Verena; van Tulder, Raphael; Havel, Christof; Schreiber, Wolfgang; Rasoul‐Rockenschaub, Susanne; Wrba, Thomas; Herkner, Harald; Laggner, Anton N.; Roth, Dominik
Abstract: Objective: Early diagnosis or rule‐out of acute coronary syndrome (ACS) is a key competence of emergency medicine. Changes in the NSTE‐ACS guidelines of the European Society of Cardiology (ESC) in 2015 and 2020 both warranted a henceforth more conservative approach regarding high‐sensitivity troponin t (hsTnt) testing. We aimed to assess the impact of more conservative guidelines on the frequency of early rule‐out and prolonged observation with repeated hsTnt testing at a high‐volume tertiary care emergency department. Patients and Methods: We conducted a pre‐ and post‐changeover analysis 3 months before and 3 months after transition from less (hsTnt cut‐off 30 ng/L, 3‐hour rule‐out) to more conservative (hsTnt cut‐off 14 ng/L, 1‐hour rule‐out) guidelines in 2015, comparing proportions of patients requiring repeated testing. Results: We included 5442 cases of symptoms suspicious of acute cardiac origin (3451 before, 1991 after, 2370 (44%) female, age 55 (SD 19) years). The proportion of patients fulfilling early‐rule out criteria decreased from 68% (2348 patients) before to 60% (1195 patients) with the 2015 guidelines ( P  < .01). Those requiring repeated testing significantly ( P  < .01) increased from 22% (743 patients) to 25% (494 patients). Positive results in repeated testing significantly ( P  = .02) decreased from 43% (320 patients) to 37% (181 patients). Invasive diagnostics were performed in 91 patients (2.6%) before and in 75 patients (3.8%) after ( P  = .02) the guideline revision. Conclusion: The implementation of the more conservative 2015 ESC guidelines led to a minor rise in prolonged observations because of an increase in negative repeated testing and to an increase in invasive procedures.